Building Equitable Decentralization in Central Papua through Reformulation of Food Security Governance Based on the Prevalence of Insufficient Consumption - Alfin Dwi Novemyanto (Institut Agama Islam Negeri Curup, 2025)
Based on data from the Central Statistics Agency (BPS) in 2024, the prevalence of inadequate food consumption in Central Papua reached 37.69%, the highest nationally. This condition reflects the weak implementation of the principle of equitable decentralization, especially in the food security sector. The research aims to analyze the relevance of the prevalence of insufficient consumption as an evaluative indicator of the performance of regional autonomy, as well as to formulate the direction of reformulation of food security governance based on the principles of asymmetric decentralization and institutional independence. The method used is normative legal research with an empirical approach, which combines statutory, conceptual and socio-juridical approaches. Data analysis is done descriptively-analytically and evaluatively to reveal the gap between legal norms and structural reality in Central Papua. The results show the dysfunction of autonomy due to the absence of adequate fiscal and institutional support. The novelty of this research lies in the placement of food consumption indicators as a juridical benchmark for the effectiveness of decentralization in new autonomous regions. The scientific contribution of this research reinforces the urgency of preparing data-based affirmative policies and structured institutional designs to ensure the fulfillment of the right to food within the framework of substantive regional autonomy.